Spiral Model Sebagai SDLC Method Pada Sistem Informasi Desa (SIMDES) - Wina Yusnaeni; Aday Hariri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
Village Administrative Services are done in the village office, village information is also done by way of door-to-door system. This resulted in the process of delivering information fairly long. In addition, residents who want to make a submission must come to the village office and wait on the spot or will return with a period of more than one day. The purpose of this study is to provide a container in the form of online information system in the form of web-based village administration services, where residents can get Village information by opening the website. In addition, residents can submit online without having to come to the village submission place. In the design of Village information system using spiral model as Software Development Life Cycle (SDLC) method. Needs analysis made has three pages, namely the main page, admin page and community page. In its design consists of the design of the database, namely ERD, input and output document design and navigation structure as the design of the admin and community web page menu. For the programming language used is PHP by using the Framework. Applications created in trials with unit testing using blackbox testing as an evaluation of the application is successful or not.